Sedekah Sampah (Waste Donation) As a Social Innovation Model Based on Environmental Education: A Systematic Literature Review - Imas Siti Masuroh; Ghullam Hamdu (International Journal of Nusantara Islam, 2026)
This study aims to analyze the intellectual development and conceptual structure of waste donation as a social innovation model grounded in environmental education within the circular economy framework. The key concepts include waste donation, ecological philanthropy, Prosocial Behavior Theory, circular economy, and social capital. Employing a Systematic Literature Review (SLR) approach based on PRISMA 2020 guidelines and bibliometric analysis using VOSviewer, this research examines 84 Scopus-indexed articles published between 2006 and 2026. The scope of analysis encompasses waste redistribution practices across environmental management, public health, and community governance domains. The findings reveal three dominant thematic clusters: environmental performance and waste reduction, social empowerment and community solidarity, and institutional governance. However, prosocial and religious dimensions remain underrepresented in mainstream sustainability discourse. Major challenges include theoretical fragmentation, limited longitudinal studies, and insufficient economic evaluation. The study recommends integrating Prosocial Behavior Theory into circular economy analysis to strengthen the moral and social foundations of sustainable waste governance. This research contributes to circular economy theory and environmental sociology by reconceptualizing waste donation as ecological philanthropy, bridging environmental sustainability with moral solidarity and social capital formation.